2018
DOI: 10.7717/peerj.5403
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on creativity: an exploration of convergent and divergent thinking

Abstract: Previous studies on the genetic basis of creativity have mainly focused on the biological mechanisms of divergent thinking, possibly limiting the exploration of possible candidate genes. Taking a cognition-based perspective, the present study investigated the genetic basis for both the divergent and the convergent thinking components of creativity. A total of 321 Chinese university students were recruited to complete the Guildford Unusual Using Test (UUT) for divergent thinking capability and the Remote Associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Besides classic insight problems, there have been attempts to examine the association of COMT with other insight tasks, such as RAT. In a recent study aimed to explore the genetic correlates of convergent and divergent thinking, Han et al (2018) investigated the association of two COMT SNPs (rs4680 and rs5993883) with RAT performance. However, to make things more complicated, this study yielded somewhat different results compared to those obtained from our study and the study conducted by Jiang, Shang & Su (2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides classic insight problems, there have been attempts to examine the association of COMT with other insight tasks, such as RAT. In a recent study aimed to explore the genetic correlates of convergent and divergent thinking, Han et al (2018) investigated the association of two COMT SNPs (rs4680 and rs5993883) with RAT performance. However, to make things more complicated, this study yielded somewhat different results compared to those obtained from our study and the study conducted by Jiang, Shang & Su (2015).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that both the rs4680 and rs4633 polymorphisms were significantly associated with insight problem solving and the rs5993883 polymorphism demonstrated a significant gender-dependent effect, with the association only present in males. Based on these findings, Han et al (2018) further examined whether two of the previously reported COMT SNPs (rs4680 and rs5993883) were associated with performance in the Remote Associates Test (RAT; Mednick, 1962), which is also commonly used to assess insight problem solving (Bowden et al, 2005). However, the results demonstrated that only the rs5993883 polymorphism was associated RAT performance.…”
Section: Introductionmentioning
confidence: 99%
“…Besides classic insight problems, there have been attempts to examine the association of COMT with other insight tasks, such as RAT. In a recent study aimed to explore the genetic correlates of convergent and divergent thinking, Han et al (2018) investigated the association of two COMT SNPs (rs4680 and rs5993883) with RAT performance. However, to make things more complicated, this study yielded somewhat different results compared to those obtained from our study and the study conducted by Jiang et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 36 papers on the general creative thinking process employed RAT. Studies on the general creative thinking process explored how the incubation mechanism (such as sleep, fixation, inhibition, and dreaming) affects creative thinking (Zhong et al, 2008;Sio et al, 2013;Smith et al, 2013;Koppel and Storm, 2014;Whitehurst et al, 2016;Carlsson et al, 2019), how individuals' memory, such as working memory and memory retrieval, affects creative thinking (Ricks et al, 2007;Dewhurst et al, 2011;Storm et al, 2011;Gómez-Ariza et al, 2017;Beda and Smith, 2018;Wang et al, 2019), how attention span enhances the output of creative ideas (Ansburg and Hill, 2003;Schmajuk et al, 2009;Zmigrod et al, 2015;Wronska et al, 2018), the association between creative thinking and how the brain works (such as brain networks, brain structure, brain function, and brain waves) (Razumnikova, 2007;Cerruti and Schlaug, 2009;Brunyé et al, 2015;Aberg et al, 2017;Godwin et al, 2017;Colzato et al, 2018;Dong, 2018;Hertenstein et al, 2019;Li et al, 2019;Peña et al, 2019;Schuler et al, 2019), and how priming (Moss et al, 2011;Chiu and Tu, 2014;Radel et al, 2015;Baror and Bar, 2016), metacognition (Ackerman and Beller, 2017), analogy (Jones and Estes, 2015), colors (Xia et al, 2016), genes (Han et al, 2018), and intelligence (Mussel et al, 2015) inf...…”
Section: General Creative Processmentioning
confidence: 99%